A Glimpse into the Past. The Joseph Ternbach Collection. Foreword by Teddy Kollek. Introduction by R. Merhav - Merhav, Rivka et al. (1981)
KeiBi-relevant: 25-54, R. Merhav - A. Shaffer, Mesopotamia (i.a. bronze model chariot and foundation peg figurine, ED III; peg with couchant animal, Neo-Sumerian; clay nail, Lipit- Ištar 2; stone tablet, Gudea; OB clay tablets; four cylinder seals, ?emdet